Peake's commentary on the Bible - Peake, Arthur Samuel, 1865-1929; Black, Matthew; Rowley, Harold Henry, 1890-1969 (London, UK Thomas Nelson, 1962)
Includes bibliographical references, indexes, maps, etc.
A.S. Peake edited this work for its first 1919 edition, hence the title.
Keywords: Bible -- commentaries